Independent Functioning in Nonagenarians Living in a Rural Italian Community: The Mugello Study. (March 2020) - Cecchi, F.; Pancani, S.; Molino-Lova, R.; Castagnoli, C.; Paperini, A.; Boni, R.; Gori, G.; Macchi, C.
Nonagenarians are a fast-growing population deserving specific research. We explored the prevalence and characteristics of functionally independent nonagenarians from a rural community-dwelling Italian population. Data were collected in the Mugello Study; 475 persons aged ≥90 years (median age, 92) underwent a home-based clinical and functional assessment, including psychosocial, clinical, functional, and lifestyle history and status and physical and instrumental examinations. Sixty-eight (15%) persons reported no need for help in basic and instrumental daily living activities. Among variables significantly associated with independent functionality after age- and gender-adjusted cross-sectional analysis, lower body mass index (BMI; p = .034) and depressive symptoms ( p = .028), higher current physical activity ( p < .001), better cognitive status ( p = .033), and lower medication intake ( p = .048) were associated with reporting no disability in the logistic regression analysis. Disability was mainly associated with current lifestyle-related potentially modifiable factors. Thus, lifestyle-oriented multidimensional interventions, should be developed and evaluated for their potential effects on functionality, even in the oldest old.